(untitled) - Ching, Julia (Tokyo, 1977)
The underlying idea presented in this book is that there are similarities as well as differences between Confucianism and Christianity as a theocentric religion, and that these similarities and differences are mutually involved and delicately related
Keywords: Nho giáo,Confucianism; Mối quan hệ,Kitô giáo,Relations,Christianity